Pelatihan Senam Yoga Pada Wanita Diabetes Mellitus Di Wilayah Kerja Puskesmas Tamalanrea Makassar - Sriwahyuni; Sri Darmawan; Kartika Sari Wijayaningsih (Jurnal Informasi Pengabdian Masyarakat, 2023)
Diabetes is a degenerative disease that is directly related to lifestyle, characterized by an increase in blood sugar levels due to abnormalities in insulin secretion. The prevalence of Diabetes Mellitus in Indonesia is diagnosed at 1.5%, in South Sulawesi Province in 2014 the number of Diabetes Mellitus cases was (282 thousand sufferers). Therefore, the attitude of sufferers and the role of health workers and those closest to them are very important in influencing behavior in controlling blood sugar levels. which is at risk of complications. One effort to control type 2 diabetes is non-pharmacological, such as yoga, which is an alternative that can be done to lower blood sugar levels which is considered to have a positive effect and can be done independently by the patient at home. In this activity, the main target was women suffering from diabetes mellitus, as many as 20 participants who were given yoga exercise training in the working area of ​​the Tamalanrea Makassar health center. From the evaluation results it was found that there was an increase in knowledge and changes in behavior to better understand and be able to carry out yoga physical activities independently. It is hoped that yoga exercise activities can be carried out every week in order to maintain stable blood sugar levels, so it can be concluded that all participants are able to carry out yoga exercise activities independently.